Salvage of Infected Breast Implants - Joon Ho Song (Archives of Plastic Surgery, 2017)
Background Implant-based breast reconstruction is being performed more frequently, and implants are associated with an increased risk of infection. We reviewed the clinical features of cases of implant infection and investigated the risk factors for breast device salvage failure. Methods We retrospectively analyzed 771 patients who underwent implant-based breast reconstruction between January 2010 and December 2016. Age, body mass index, chemotherapy history, radiation exposure, and smoking history were assessed as potential risk factors for postoperative infection. We also evaluated the presence and onset of infection symptoms, wound culture pathogens, and other complications, including seroma, hematoma, and mastectomy skin necrosis. Additionally, we examined the mastectomy type, the use of acellular dermal matrix, the presence of an underlying disease such as hypertension or diabetes, and axillary node dissection. Results The total infection rate was 4.99% (58 of 1,163 cases) and the total salvage rate was 58.6% (34 of 58). The postoperative duration to closed suction drain removal was significantly different between the cellulitis and implant removal groups. Staphylococcus aureus infection was most frequently found, with methicillin resistance in 37.5% of the cases of explantation. Explantation after infection was performed more often in patients who had undergone 2-stage expander/implant reconstruction than in those who had undergone direct-to-implant reconstruction. Conclusions Preventing infection is essential in implant-based breast reconstruction. The high salvage rate argues against early implant removal. However, when infection is due to methicillin-resistant S. aureus and the patient’s clinical symptoms do not improve, surgeons should consider implant removal.